Seropidemiology Of Human Hydatidosis In Kirkuk And Tikrit/ Iraq - Kadir, Mohammed Abdul- Aziz; Adil, Suzan; AL-Den, Suhela Shams (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Hydatid disease is a serious infection of man caused by larval stage (hydatid) of the small dog tapeworm. Serological tests are important in the diagnosis of hydatid disease. Objectives: The study was carried out to detect the rate of seropositivity of hydatid cysts in Kirkuk and Tikrit cities. Materials and Methods: The retrospective hospital based and seroepidemiological studies were carried out in Kirkuk and Tikrit cities, during the period from beginning of January 2000 until the end of October 2003. The hospital based study included 125-hydatid cyst operations in hospitals of Kirkuk (82) and Tikrit (43). The serological tests used for detection of hydatid cysts antibody were latex agglutination test (LA) and enzyme linked immunosorbent assay (ELISA). The seroepidemiological study included 288 individuals from different groups of populations: veterinarians (42), animal breeders (36), butchers (78), housewives (45), children (30) and other occupations (57). Results: The rate of hydatid cysts operation in males (41.6%) was lower than females (58.4%). The highest rate of operation was at the age group between 21-30 years old (26.4%) and the lowest was among 51-60 years (12.8%). The highest rate of operation was sited in liver 91 (72.8%) followed by lung 19 (15.2%) and other sites 15 (12%). The rate of seropositivity among different groups of occupation by using ELISA and LA tests were as follows: veterinarians (78.5% & 57.14%), animal breeders (58.3% & 22.22%), butchers (57.6% & 43.58%), housewives (60.0% & 48.8%), children (60.0% & 33.33%) and other occupations (38.6% & 21.05%) respectively. The rate of seropositivity in females was higher than males in both tests. In ELISA the rate in females and males was 74.1% and 51.20%, while in LA test the rate in females and males was 49.38% and 33.8 % respectively. The distribution of seropositivity varied in different age groups. The highest rate was among the age group 31-40 years in both ELISA (74.07%) and LA (55.5%) tests. Conclusions: The prevalence of hydatid disease in man was high in Kirkuk and Tikrit cities. The highest rate of seropositivity was among veterinarians followed by house wives, children and animal breeders. The ELISA test was more sensitive than LA for detection of seropositive cases of hydatid disease.